(x-2)(x+4)=4

Simple and best practice solution for (x-2)(x+4)=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-2)(x+4)=4 equation:



(x-2)(x+4)=4
We move all terms to the left:
(x-2)(x+4)-(4)=0
We multiply parentheses ..
(+x^2+4x-2x-8)-4=0
We get rid of parentheses
x^2+4x-2x-8-4=0
We add all the numbers together, and all the variables
x^2+2x-12=0
a = 1; b = 2; c = -12;
Δ = b2-4ac
Δ = 22-4·1·(-12)
Δ = 52
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{52}=\sqrt{4*13}=\sqrt{4}*\sqrt{13}=2\sqrt{13}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(2)-2\sqrt{13}}{2*1}=\frac{-2-2\sqrt{13}}{2} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(2)+2\sqrt{13}}{2*1}=\frac{-2+2\sqrt{13}}{2} $

See similar equations:

| 3(2x-7)-4x=19 | | 4x1=x+7 | | 4x−8=6x+16 | | 121-x=59 | | 10=-4(x-6) | | 6y2+5y−6=0 | | 33/4b=300 | | P(3)=2/5x+1/2 | | 10=-4(x+-6) | | 13=a-15 | | 10=-4(x+11) | | 44+f=128 | | 3^-8x=14^-x-5 | | (8x+7)(2x+8)=45 | | 156.5+w=222.87 | | -6y-3=3-7y | | 9.64x10x12(x)=4.78 | | 20x2+9x+1=0 | | 6s+12=3(2s=8) | | -8x-64=31-13x | | F(5)=7x+2 | | y-98=444 | | 8(x-3)=-(5x-11) | | 7.49x10^-28=3.98x | | -50+3x+x=-11 | | -x=x-24 | | 11x-2(3x+5)=3(x+4) | | 1y+1y=−4y+8 | | y-33.9=25.4 | | -6x-9=-3(x-12) | | Z13.1-0.7z=8.2 | | X+5(2-x)-3=15 |

Equations solver categories